Considering the first randomized trial of peroral endoscopic myotomy versus surgical myotomy for achalasia - Şİmşek, Cem (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Şimşek C. Considering the first randomized trial of peroral endoscopic myotomy versus surgical myotomy for achalasia. Turk J Gastroenterol 2020; 31(2): 190-192